Effect of short-term exposure to ambient air particulate matter on incidence of delirium in a surgical population. Issue 1 (December 2017) - Che, Lu; Li, Yan; Gan, Cheng
Abstract Delirium remains an independent risk factor for morbidity and mortality among older surgical adults. Recent research has shed light on the relationship between pollution and dementia, yet little is known about the health impacts of particulate matter (PM) on delirium. Therefore, we aim to further explore association of PM and delirium among surgical population. We conducted a time-stratified case-crossover study. Electronic hospitalization summary reports derived from 26 major cities in China between 1 January 2014 and 31 December 2015 were used. Conditional logistic regression were applied to explore the association between perioperative PM exposure and delirium. A total of 559 surgical patients with delirium were identified. Both PM2.5 and SO2 on the day of surgery had a negative impact, with an interquartile range (IQR) increase in PM2.5 (47.5 μg/m 3 ) and SO2 (22.2 μg/m 3 ) significantly associated with an 8.79% (95% confidence interval [CI], 0.01–18.47%, P < 0.05) and 16.83% (95% CI, 0.10–36.35%, P < 0.05) increase in incidence of delirium, respectively. PM on other days during the perioperative period showed no significant impact. The present study showed that short-term exposure to ambient air PM on the day of surgery increased the incidence of delirium in a surgical population during hospitalization.